Ion acceleration via 'nonlinear vacuum heating' by the laser pulse obliquely incident on a thin foil target. (7th December 2015) - Yogo, A; Bulanov, S V; Mori, M; Ogura, K; Esirkepov, T Zh; Pirozhkov, A S; Kanasaki, M; Sakaki, H; Fukuda, Y; Bolton, P R; Nishimura, H; Kondo, K
Abstract: The dependence of the energy of ions accelerated during the interaction of the laser pulse obliquely incident on the thin foil target on the laser polarisation is studied experimentally and theoretically. We found that the ion energy being maximal for the p -polarisation drastically decreases when the pulse becomes s -polarised. The experimentally found dependencies of the ion energy are explained by invoking anomalous electron heating, which results in high electrostatic potential formation at the target surface. The anomalous heating of electrons beyond the energy of quiver motion in the laser field is described within the framework of a theoretical model of a driven oscillator with a step-like nonlinearity. We have demonstrated that the electron anomalous heating can be realised in two regimes: nonlinear resonance and stochastic heating, depending on the extent of stochasticity.